The urban existence of Baghdad city between the effect of the provisions of the construction of jurisprudence and Contemporary Urban legislation - Ali, Amjed M. (Sulaimani Journal for Engineering Sciences, 2014)
The ruling mechanism of the urban environment Arabic Islamic cities in the past differs from similar current ones, for the affairs of urbanism and constructions, in those cities, were mainly administrated through the system of "religions legislations"(Feqqh) that used to run all aspects of life in a total state of equilibrium, this system, which re gave birth to a highly distinct homogeneous environment conveying not only the needs and requirements of its occupants, but also their culture and ambitions. Growing , interactionally, with their customs , ethics and values. In the current urban- environment, substantial change has accrued at the legislational system that runs and controls the affairs of the urban construction extended to cover the roots and shoots, most of which were imported or inspired from a different environment, which a different kind of constants and variables of those of the local environment, This has led to multi-level controversial and negative aspects, troubled the occupants of the current cities and towns, and that was the main problem of this research. This study aimed to convey a picture of the reality of Baghdad city under the system that used to run its constructional affairs previously - religions legislations and law - and take it as a base of view, to look through it to the reality of the Arab Islamic city of today under current constructional legislations, and this study shown the main urban problems and the extent of the participation of these constructional legislations in the said problems, taking the capital of Baghdad as a realistic case of study for the current Arabian-Islamic city; documenting some of its aspects and questioner a section of its inhabitants; to know their points of view concerning the problems they face and their causes, to conduct a general comparing between the most important features of the traditional and current environments, each under its special legislations. This study showed the most important urban problems caused by that “contemporary” legislation, and also showed the presence of considerable support in the study area for the point of view of jurisprudence legislation in urban issues, as opposed to the perspective of contemporary urban legislation.